Literature Review on the Use of Interactive Labs Technology in The Context of Science Education - Ni Nyoman Sri Putu Verawati; Agus Abhi Purwoko (Faculty of Engineering and Applied Science, 2024)
Science education is a cornerstone in preparing students for the complexities of the contemporary world. In this vein, the integration of Interactive Labs technology resources into science learning presents a promising avenue. This literature review delves into the expansive realm of Interactive Labs within science education, shedding light on their myriad advantages and burgeoning trends. Employing the